Low-loss curved waveguide grating wavelength demultiplexer - Hadij-El-Houati, Abdelfettah; Ortega-Moñux, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Halir, Robert; Wang, Shurui; Schmid, Jens H.; Cheben, Pavel; Molina-Fernández, Íñigo (My University, 2021)
We demonstrate a compact wavelength demultiplexer for the silicon on insulator platform based on the curved waveguide grating (CWG) architecture. We mitigate off-chip radiation loss by enforcing the single beam condition by using metamaterial index engineering. The fabricated device exhibits insertion loss as low as 1dB and crosstalk lower than -25 dB.
Keywords: Telecomunicaciones - Congresos; Wavelength demultiplexer; Low-loss curved waveguide